Pengaruh Budaya Organisasi terhadap Kepuasan Kerja Guru Yayasan Prajnamitra Maitreya Pekanbaru - Suryati Suryati; Nyoto Nyoto; Sudarno Sudarno (Jurnal Maitreyawira, 2022)
ABSTRACT The Prajnamitra Maitreya Pekanbaru Foundation faces the challenge of increasing teacher job satisfaction through the application of a school organizational culture with characteristics of educational background, ethnicity, religion, and different character and mindset of teachers. The purpose of this study is to analyze the influence of organizational culture on teachers’ job satisfaction. The number of samples in this study was the entire study population of 57 teachers at Prajnamitra Maitreya Foundation Pekanbaru. The Likert Scale is used for collecting survey data. This research using Smart PLS (Partial Least Squares) for revealed that organizational culture has significant effect on job satisfaction